2013
DOI: 10.4081/vsd.2013.e3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrapathological evaluation of the anticancer effect of blackseed (Nigella sativa) and garlic (Allium sativum) in mice

Abstract: In this experimental work, 120 virgin female mice (body weight 40±10 gm) were divided into 6 equal groups. Mice in Group 1 served as a control. Mice in Groups 2 and 3 were fed on a basal diet provided with 100 mg/kg b.wt from each of blackseed (Nigella sativa) and garlic (Allium sativum), respectively, for one month. Mice in Group 4 were inoculated subcutanously (S/C) with Ehrlich tumor cells after one month from the start of the experiment. Mice in Groups 5 and 6 were treated similarly to those in Groups 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In these studies, dietary garlic in mouse feed enhanced proliferation of lymphocytes and neutrophils. The garlic metabolite, allicin, also increased pokeweed mitogen‐induced human peripheral blood mononuclear cells (PBMCs) proliferation in a dose‐dependent manner (Salman et al., ; Nouh, ). On the other hand, these results also showed that phytogenic extracts and a mixture of phytogenic extracts and probiotics did not have a cytotoxic effect to S‐LPLs and L‐LPLs.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, dietary garlic in mouse feed enhanced proliferation of lymphocytes and neutrophils. The garlic metabolite, allicin, also increased pokeweed mitogen‐induced human peripheral blood mononuclear cells (PBMCs) proliferation in a dose‐dependent manner (Salman et al., ; Nouh, ). On the other hand, these results also showed that phytogenic extracts and a mixture of phytogenic extracts and probiotics did not have a cytotoxic effect to S‐LPLs and L‐LPLs.…”
Section: Resultsmentioning
confidence: 99%